Transdiagnostic school‐based intervention for adolescents with early persistent psychiatric symptoms: An initial single‐group effect study. Issue 5 (26th November 2018) - el Bouhaddani, Saliha; Veling, Wim; Schaefer, Barbara; Doreleijers, Theo; van Domburgh, Lieke
Abstract : Aim: Mental health intervention programs for adolescents generally focus on specific symptoms, such as anxiety or depression. Psychiatric symptoms in adolescence are often heterogeneous, transient and shift over time. These characteristics require a transdiagnostic approach with emphasis on positive psychological development. This study aimed to examine the feasibility and effectiveness of Mastermind, a novel transdiagnostic intervention targeting general underlying mechanisms of psychiatric symptoms in adolescents. Methods: Adolescents were screened for psychiatric symptoms with the Strengths and Difficulties Scale in a school‐based program in two consecutive years. Adolescents were eligible for the intervention when they had psychiatric symptoms at both screening assessments. Participants received an 8 weeks program containing elements of empowerment and attention bias modification. Psychiatric symptoms were assessed before the start of the intervention, immediately after the intervention and at 6‐month follow‐up. Results: A total of 241 adolescents were eligible for the intervention, of whom 80 participated (mean age 12.5 years). Generalized Estimating Equations, adjusted for gender and educational level, showed a decrease of negative attention bias, psychotic, anxiety, depression and behavioural symptoms immediately after intervention. The effects remained at follow‐up. Overall risk for psychiatric disorders, distress and low self‐esteem had decreased at follow‐up. Conclusions: A simple two‐step school‐based screening can identify adolescents with persistent psychiatric symptoms. The Mastermind transdiagnostic group intervention may be effective to reduce psychiatric symptoms, enhance self‐esteem and lower the risk for developing psychiatric disorders.